Leaf Na+ effects and multi-trait GWAS point to salt exclusion as the key mechanism for reproductive stage salinity tolerance in rice - de Ocampo, Marjorie P.; Tam, Bui Phuoc; Egdane, James A; Chebotarov, Dmytro; Doi, Kazuyuki; Yamauchi, Akira; Ismail, Abdelbagi M; Henry, Amelia; Mitsuya, Shiro (Oxford University Press, 2025)
Background and Aims Since salinity stress may occur across stages of rice (Oryza sativa L.) crop growth, understanding the effects of salinity at reproductive stage is important although it has been much less studied than at seedling stage. Methods In this study, lines from the Rice Diversity Panel 1 (RDP1) and the 3000 Rice Genomes (3KRG) were used to screen morphological and physiological traits, map loci controlling salinity tolerance through genome-wide association studies (GWAS), and identify favorable haplotypes associated with reproductive stage salinity tolerance. Key Results Salt exclusion was identified as the key tolerance mechanism in this study based on reduced panicle length as flag leaf Na+ increased, and a lack of effect of trimming the leaves in the salinity treatment on genotypic rankings. Since larger biomass showed a negative effect on the number of filled grains in multiple experiments, future studies should investigate the effect of whole-plant transpiration levels on salt uptake. In addition to genome-wide significant peaks identified in the single trait GWAS analyses, six loci showed colocations for multiple traits across experiments. Among these co-locating loci, three candidate loci that exhibited favorable haplotypes were also characterized to be involved in co-expression networks among which apoplast and cell wall functions had been annotated – further highlighting the role of salt exclusion. Conclusion The loci identified here could be considered as potential sources for improving reproductive stage salinity tolerance in rice.